(3eNJUQ cJGH GdYdd hGdCYQGV dLGdjfhSs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3Ydi Hf EHQGgje Hf CMeO GdJLjHi s)
(3ChdgG (B:s
(3ddabjg GHf QTO cdGe ai GNJUGQ GdYdd hGYQGV dLGdjfhS , hPdc Cfg MPa efg GdJWhjd hGdMTh , hPcQ ef cdGeg eGgh ZQVg ai GdebGdI s
(3BNQgG (B:s
(3hgfG GfbVi cdGeg Ydi GdYdd hGdCYQGV HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQg eY JdNjU cJGH GdMejGJ Qbe (B" 423"s
(3hGVM ef ebOeI GdcJGH Cfg eNJUQ GNJUGQ GHf QTOs
(3GdfGSN gh cGJH GdeLehYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdWHs